The Influence of Celebrity Endorser, Price, and Social Media on Purchase Decisions Mediated by Brand Image (Empirical Study: Shopee Consumers in Jakarta) - Yenni, Yenni; Sugiyanto, Liem Bambang (Asian Journal of Social and Humanities, 2023)
This study aims to identify the factors influencing purchasing decisions on the shopee e-commerce platform. It analyzed factors such as celebrity endorser, price, and social media influence the purchase decision in Jakarta City, both directly and indirectly mediated by brand image. The research used quantitative methods and was processed using AMOS. The survey was conducted on 15o respondents who met the respondent criteria using purposive, non-probability sampling. The research found that celebrity endorsers and social media did not significantly influence the purchase decision. Meanwhile, price and brand image had a significant influence on purchase decisions. However, after being mediated by brand image, celebrity endorsers showed a more significant influence on purchase decisions. Social media also showed a more significant influence on purchase decisions. In contrast, price's influence on purchase decisions was less significant even after being mediated by brand image. The limitation of the research was the limited respondents, with 150 respondents domiciled in Jakarta who had purchased on the shopee e-commerce platform. This research could be generalized more widely if the samples were taken not only from Jakarta City. The implications of this research provided managerial contributions to the online shop industry, especially an overview of online consumer behavior and an understanding of the factors influencing increased purchase decisions, such as celebrity endorsers, prices, social media, and brand image, so merchants can develop a business strategic plan that aligns with internal and external company conditions.